Novel rapid PCR for the detection of Ile491Phe rpoB mutation of Mycobacterium tuberculosis, a rifampicin-resistance-conferring mutation undetected by commercial assays. (April 2017) - André, E.; Goeminne, L.; Colmant, A.; Beckert, P.; Niemann, S.; Delmee, M.
Abstract: Objectives: Neither the liquid medium-based Bactec MGIT, nor commercial molecular assays such as the Xpert MTB/RIF and the MTBDR plus V2.0 assays are capable of detecting up to 30% of rifampicin-resistant Mycobacterium tuberculosis strains in Swaziland because of the large proportion of the rpoB Ile491Phe mutations. In other countries, the frequency of this mutation is thought to be low. Methods: We designed a real-time multiplex allele-specific PCR assay to identify the rpoB Ile491Phe mutation responsible for these undetected resistant M. tuberculosis strains. Results: The technique showed 100% similarity with rpoB sequencing on a panel of 78 strains from Swaziland. Conclusions: We propose that the detection of the rpoB Ile491Phe rpoB mutation should complement commercial assays for the diagnosis of rifampicin-resistant M. tuberculosis in routine conditions, particularly in countries where this specific mutation is frequent. The technique proposed in this paper is adapted for most reference laboratories.